Islamic Education and Local Governance: A Collaborative Framework for Combating Child Marriage - Andi Utari Samsir; Ahmad Muktamar; Muhaemin Muchlis; Fitriani Fitriani; Reski Amaliah; Hasdi Anugrah; Muh. Akmal Mubaraq; Lailatil Qadriani; Aulia Novita Handayani (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Early marriage in Welado Village, Indonesia, remains a persistent developmental challenge, driven by cultural resistance and superficial religious internalization. This study analyzes the educational collaboration between village government and the community in mitigating early marriage, examining the role of Islamic education in enhancing collaborative effectiveness. Utilizing a descriptive-qualitative approach, data were gathered through in-depth interviews, participatory observation, and documentation with key local stakeholders. Analysis followed data reduction, display, and verification stages, framed around five collaboration dimensions: common purpose, mutuality, enabling environment, trust, and specific personal characteristics. The findings reveal that while common purpose, mutuality, and enabling environments function optimally through shared educational visions, significant constraints persist within trust and specific personal characteristics due to negative public perception and weak cross-sectoral coordination. From an Islamic education perspective, these structural-cultural barriers occur because the core tenets of maslahah (public good), amanah (trustworthiness), and akhlaq (character formation) remain unintegrated into the collaborative framework, rendering existing approaches merely administrative. Theoretically, this study pioneers a community-empowerment-based model of Islamic education. Practically, it underscores the necessity of embedding Islamic educational values as a moral-spiritual foundation within village policies to foster transformative collective awareness for early marriage eradication.